2018
DOI: 10.1055/a-0577-2560
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection for early esophageal cancer in elderly patients with relative indications for endoscopic treatment

Abstract: Based on this study, regular follow-up without additional treatment may be considered as another choice for elderly patients with early esophageal SCC and relative indications after ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 31 publications
3
32
2
Order By: Relevance
“…For this reason, we concluded that additional treatment is necessary for cases with lymphovascular involvement and/or positive margin in the histopathology specimen to decrease risk of recurrence and improve survival. That has already been described previously by other authors for curability criteria [9,15]. In our cases, the first line for additional therapy was surgery (3FLD), and chemotherapy for patients who were not eligible for surgical treatment, to avoid recurrence and complications as described in past studies of post-recurrence cases [16].…”
Section: Discussionsupporting
confidence: 70%
“…For this reason, we concluded that additional treatment is necessary for cases with lymphovascular involvement and/or positive margin in the histopathology specimen to decrease risk of recurrence and improve survival. That has already been described previously by other authors for curability criteria [9,15]. In our cases, the first line for additional therapy was surgery (3FLD), and chemotherapy for patients who were not eligible for surgical treatment, to avoid recurrence and complications as described in past studies of post-recurrence cases [16].…”
Section: Discussionsupporting
confidence: 70%
“…Pre-operative EUS and CT were routinely performed. The study excluded 10 cases of ESD with additional treatment [ 30 ]. The rate of complete resection was 99.4%.…”
Section: Long-term Outcomes Of Esd For Superficial Esophageal Squamentioning
confidence: 99%
“…In our study, we investigated additional treatment options and long‐term outcomes of patients who were confirmed to have SMI or LVI after endoscopic resection. We speculated that elderly patients tend to refuse additional treatment such as surgery or CCRT because of their physical status and the psychological burden of additional treatment . However, in this study, the proportion of patients who did not undergo additional treatment was similar between the two groups.…”
Section: Discussionmentioning
confidence: 61%